The Development of Father Involvement Scale for the Indonesian Cultural Context (FIS-IV) - Fitria Lestari, Rida; Surya, Dedy (Jurnal Psikologi Islam dan Budaya, 2026)
Research on father involvement in Indonesia frequently utilizes Western instruments that lack local cultural context. This study aimed to develop and validate the Father Involvement Scale: Indonesian Version (FIS-IV) using the Rasch model. Employing a methodological design, data were collected from 600 adolescents (ages 12–21) via purposive sampling and analyzed using Winsteps. Results indicated that 17 of 18 initial items met the criteria, with one misfit item removed. The scale demonstrated unidimensionality (50.4% variance), high reliability (person=.81, item=.98), adequate separation indices, and gender neutrality based on Differential Item Functioning analysis. Conceptually, the original dimensions—Engagement, Accessibility, and Responsibility—merged into a cohesive unidimensional trait suitable for the Indonesian context. Practically, the FIS-IV is a highly reliable, culturally relevant diagnostic tool. It empowers school counselors and practitioners to assess paternal support, identify "father hunger," and design targeted psychosocial interventions to improve adolescent well-being.